Clinicopathological, Immunological, and Laboratory Parameters of Childhood Lupus Nephritis: A Study from Northeast India - Das, Jonali; Kalita, Pranjal; Dey, Biswajit; Raphael, Vandana; Mishra, Jaya; Khonglah, Yookarin; Marbaniang, Evarisalin; Handique, Gauranga; Saurabh, Animesh (Journal of Laboratory Physicians, 2023)
Background Lupus nephrtis in children is associated with high morbidity and mortality. The incidence of childhood systemic lupus erythematosus (SLE) ranges from 3.3 to 8.8/100000 children with a higher Asian preponderance. The predominance of SLE in female pediatric patients increases gradually with age to the values observed in adults.Objectives To assess the clinical, immunological, and histopathological spectrum of childhood lupus nephritis in northeast India and explore the relationship between clinical, biochemical, serological, and histopathological findings.Materials and Methods A retrospective descriptive study was performed over 8 years. Histopathology slides were reviewed by two pathologists, whereas other details were collected from patients' records.Statistical Analysis Statistical analysis was based on the chi-square test and a p-value < 0.05 was considered statistically significant.Results Fifty-three cases of lupus nephritis were included in the study. The patients' age ranged from 5 to 18 years with a mean age of 14.5 years and a female: male ratio of 6.5:1. Edema and hypertension were the commonest clinical presentations, whereas proteinuria was the commonest presenting laboratory parameter. Amongst all the immunological markers, dsDNA was the commonest. Histopathologically, predominantly study population belonged to class IV lupus nephritis. The patients with class IV showed a statistically significant correlation with proteinuria and hematuria at the time of diagnosis. Immunological markers, namely, ANA and anti-ds-DNA positivity were significantly associated with advanced renal histopathology.Conclusion cSLE in northeast India presents mostly as Class IV LN presenting mostly with deranged laboratory parameters and preponderance of various immunological markers and clinical presentations.
Keywords: systemic lupus erythematosus; childhood lupus nephritis; class IV lupus nephritis